Delamination of Z-pinned carbon fibre reinforced laminates - Cartié, Denis D. R.; Troulis, Manos; Partridge, Ivana K. (Elsevier, 2005)
The paper outlines the current status of mechanical testing, identification of failure mechanisms and data analysis related to delamination cracking in high performance laminates made via the prepreg/autoclave route, strengthened in the through-thickness direction by Z-pinning. The applied loading cases under consideration are limited to Mode I and Mode II. Sample preparation, test methodologies and applicability of data reduction schemes are considered, with data obtained from within the range of aerospace and Formula 1 grades of carbon fibre / epoxy composites. Micromechanisms of failure in the three dimensional tests specimens are shown to be dependent on the architecture of the fibre reinforcement (i.e. unidirectional versus woven fabric prepregs), particularly in the case of Mode II loading.